2012
DOI: 10.1128/aac.05872-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Micafungin, Caspofungin, and Anidulafungin against a Difficult-To-Treat Fungal Opportunistic Pathogen, Candida glabrata

Abstract: The aim of this study was to compare the in vitro and in vivo activities of micafungin, caspofungin, and anidulafungin against Candida glabrata. The MICs against 28 clinical isolates showed that the overall susceptibilities to caspofungin and to micafungin were not statistically different in the absence of human serum, whereas the isolates were less susceptible to micafungin than to caspofungin in its presence. Minimum fungicidal concentrations, as well as time-kill experiments, showed that caspofungin was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
26
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 31 publications
11
26
1
Order By: Relevance
“…In agreement with other studies (Andes et al, 2010;Fernández-Silva et al, 2014;Gil-Alonso et al, 2015;Lepak et al, 2012;Pfaller et al, 2011;Spreghini et al, 2012;Szilágyi et al, 2012), caspofungin showed excellent in vitro activity against WT clinical isolates as well as against the ATCC 90030 type strain. However, in RPMI 1640, caspofungin killing activity decreased at 16-32 mg l 21 when compared with the killing at 0.25-1 mg l 21 (Table 3).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In agreement with other studies (Andes et al, 2010;Fernández-Silva et al, 2014;Gil-Alonso et al, 2015;Lepak et al, 2012;Pfaller et al, 2011;Spreghini et al, 2012;Szilágyi et al, 2012), caspofungin showed excellent in vitro activity against WT clinical isolates as well as against the ATCC 90030 type strain. However, in RPMI 1640, caspofungin killing activity decreased at 16-32 mg l 21 when compared with the killing at 0.25-1 mg l 21 (Table 3).…”
Section: Discussionsupporting
confidence: 80%
“…In accordance with other authors (Andes et al, 2010;Fernández-Silva et al, 2014;Lepak et al, 2012;Spreghini et al, 2012;Wiederhold et al, 2007), WT C. glabrata clinical isolates were highly susceptible in vivo to caspofungin even at 1 mg kg 21 in mice (corresponding to a 35 mg daily dose in humans) (Cornely et al, 2011;Flattery et al, 2011;Migoya et al, 2011). Moreover, as observed previously with Candida albicans, Candida krusei and Candida inconspicua, increasing the drug dose further did not yield better efficacy (Berényi et al, 2014;Kovács et al, 2014a), i.e.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…The current first-line treatment for candidemia due to C. glabrata are echinocandin agents, such as micafungin, which are potent inhibitors of beta-glucan synthase, a critical component of the fungal cell wall [1,9]. Echinocandins are efficacious against fluconazole-resistant Candida species, however, during prolonged therapy, C. glabrata can develop reduced susceptibility even to this class [10]. C. glabrata echinocandin resistance has increased from 4.9 to 12.3% between 2001 and 2010, and among the fluconazole-resistant isolates tested, 14.1% were fluconazole/echinocandin double-resistant [11].…”
Section: Introductionmentioning
confidence: 99%